Apigenin inhibits the inducible expression of programmed death ligand 1 by human and mouse mammary carcinoma cells. Issue 2 (1st October 2016) - Coombs, Melanie R. Power; Harrison, Megan E.; Hoskin, David W.
Highlights: Apigenin inhibits interferon-γ-induced PD-L1 expression by breast cancer cells. The apigenin metabolite luteolin inhibits inducible PD-L1 expression. Interferon-γ mediated STAT1 activation is inhibited by apigenin. T cell proliferation is enhanced in the presence of apigenin-treated breast cancer cells. Abstract: Programmed death ligand 1 (PD-L1) is expressed by many cancer cell types, as well as by activated T cells and antigen-presenting cells. Constitutive and inducible PD-L1 expression contributes to immune evasion by breast cancer (BC) cells. We show here that the dietary phytochemical apigenin inhibited interferon (IFN)-γ-induced PD-L1 upregulation by triple-negative MDA-MB-468 BC cells, HER2 + SK-BR-3 BC cells, and 4T1 mouse mammary carcinoma cells, as well as human mammary epithelial cells, but did not affect constitutive PD-L1 expression by triple-negative MDA-MB-231 BC cells. IFN-β-induced expression of PD-L1 by MDA-MB-468 cells was also inhibited by apigenin. In addition, luteolin, the major metabolite of apigenin, inhibited IFN-γ-induced PD-L1 expression by MDA-MB-468 cells. Apigenin-mediated inhibition of IFN-γ-induced PD-L1 expression by MDA-MB-468 and 4T1 cells was associated with reduced phosphorylation of STAT1, which was early and transient at Tyr701 and sustained at Ser727. Apigenin-mediated inhibition of IFN-γ-induced PD-L1 expression by MDA-MB-468 cells also increased proliferation and interleukin-2 synthesis by PD-1-expressing Jurkat T cells that were co-cultured with MDA-MB-468 cells. Apigenin therefore has the potential to increase the vulnerability of BC cells to T cell-mediated anti-tumor immune responses.